1995
DOI: 10.3168/jds.s0022-0302(95)76659-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation of Human Blood Cells Following the Ingestion of Lactic Acid Bacteria

Abstract: Because of the lack of data that convincingly show immunomodulatory properties of lactic acid bacteria in humans, a study was performed in which healthy volunteers were divided into two groups and given a fermented milk product supplemented with Lactobacillus acidophilus strain La1 or Bifidobacterium bifidum strain Bb 12 for 3 wk. Blood was sampled throughout the study to assess changes in lymphocyte subsets or leukocyte phagocytic activity following consumption of the fermented products. No modifications of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
231
0
17

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 484 publications
(260 citation statements)
references
References 18 publications
11
231
0
17
Order By: Relevance
“…The ability of probiotic LAB to stimulate the human immune system has been demonstrated in previous studies (de Simone et al, 1986Simone et al, , 1991Solis-Pereyra & Lemmonier, 1991;Link-Amster et al, 1994;Schiffrin et al, 1995;Kishi et al, 1996). In particular, dietary consumption of some strains of LAB has been shown to enhance cellular immune responses, including phagocytosis, lymphocyte proliferation and cytokine production (de Simone et al, 1986;LinkAmster et al, 1994;Schiffrin et al, 1995).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The ability of probiotic LAB to stimulate the human immune system has been demonstrated in previous studies (de Simone et al, 1986Simone et al, , 1991Solis-Pereyra & Lemmonier, 1991;Link-Amster et al, 1994;Schiffrin et al, 1995;Kishi et al, 1996). In particular, dietary consumption of some strains of LAB has been shown to enhance cellular immune responses, including phagocytosis, lymphocyte proliferation and cytokine production (de Simone et al, 1986;LinkAmster et al, 1994;Schiffrin et al, 1995).…”
Section: Discussionmentioning
confidence: 82%
“…It is well known that some strains of LAB can enhance cellular immune function, either innate or speci®c, when used as a probiotic (de Simone et al, 1986(de Simone et al, , 1991SolisPereyra & Lemmonier, 1991;Link-Amster et al, 1994;Schiffrin et al, 1995;Kishi et al, 1996). However, studies conducted to date have generally indicated a positive effect on one particular cellular function, such as phagocytosis or cytokine-secreting activity (Schiffrin et al, 1995;Kishi et al, 1996;Donnet-Hughes et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that phagocytic leukocyte activity of human blood cells, particularly granulocytes, is enhanced by the ingestion of fermented milk supplemented with Lactobacillus acidophilus La1 and Bifidobacterium bifidum Bb12 for 3 weeks (Schiffrin et al, 1995).…”
Section: Effects Of Probiotics On the Immune Systemmentioning
confidence: 99%
“…This was recently demonstrated with Bifidobacterium animalis subsp lactis BB-12 as well as L. reuteri ATCC 55730 (Weizman et al, 2005). It has also been suggested that probiotics may alleviate clinical symptoms of pediatric atopic diseases (Isolauri et al, 2000;Kalliomäki et al, 2001Kalliomäki et al, , 2003Rosenfeldt et al, 2003;Rosenfeldt et al, 2004) and modulate immune functions (Schiffrin et al, 1995;Fukushima et al, 1998;Blum and Schiffrin, 2003;Hart et al, 2004;Valeur et al, 2004). Concerning the effect on blood lipids contradictory results has been reported.…”
Section: Introductionmentioning
confidence: 99%